Unravelling the Potential of Seven Microalgae Species: Nutritional, Antioxidant, and Antimicrobial Properties and Application - Valter F. R. Martins; Ana I. Lopes; Diana Gomes; Celina Parreira; Sara M. Badenes; Luís Costa; Manuela Pintado; Alcina M. M. B. Morais; Rui M. S. C. Morais (Applied Sciences)
Microalgae are a rich renewable source of a wide variety of bioactive compounds. This study focuses on seven microalgae—Limnospira sp., Dunaliella sp., Lobosphaera sp., Nannochloropsis sp., Odontella sp., Porphyridium sp., and Tetraselmis sp.— analyzing their nutritional compositions and the potential bioactivity of their hydroethanolic extracts obtained via ultrasound-assisted extraction. The total phenolic content (TPC) and antioxidant activity (ABTS, DPPH, and ORAC), as well as the antimicrobial activity of the extracts were determined. The protein content of the microalgae ranged from 22.9 ± 0.1 to 59.8 ± 1.6%, the fat content ranged from 5.3 ± 0.0 to 36.6 ± 0.0%, and the carbohydrates ranged from 24.0 ± 3.0 to 46.1 ± 1.0%. The highest contents of protein, fat, and carbohydrates were found in Limnospira sp., Nannochloropsis sp., and Lobosphaera sp., respectively. The TPC of the extracts varied between 0.53 ± 0.09 and 3.18 ± 0.53 mg GAE/100 mg DW. Antioxidant activity values ranged from 1.09 ± 0.15 and 2.85 ± 0.45 μmol TE/100 mg DW for ABTS, 0.25 ± 0.06 and 2.28 ± 0.06 μmol TE/100 mg DW for DPPH, and 2.37 ± 0.58 and 18.32 ± 1.00 μmol TE/100 mg DW for ORAC. The extract from Limnospira sp. exhibited the highest antioxidant activity and also showed notable antimicrobial effects. Meanwhile, the Nannochloropsis sp. extract demonstrated the strongest antimicrobial activity against most tested bacterial strains. Lipids were successfully extracted from Nannochloropsis sp. Furthermore, alginate and zein films incorporated with bioactive-rich extracts from Limnospira sp. and Nannochloropsis sp., along with the lipid-rich extract from Nannochloropsis sp., were developed. These films showed significant antioxidant activity and effective antimicrobial activity against Listeria monocytogenes.